Preparation and characterization of nano-TiO2 doped with iron and niobium using sol-gel method - Doan, Nhat Mihn (Animo Repository, 2011)
The nanoTiO2 photocatalyst doped with iron (Fe) and niobium (Nb) for dye wastewater treatment was prepared by temperature-controlled sol-gel method. 0.1% Fe:Nb co-doped TiO2, 0.1% Fe doped TiO2, 0.1% Nb doped TiO2, bare TiO2 were compared to that of the commercially available Degussa TiO2 P25. Among these characteristics are crystal size, the presence of absolute anatase crystal phase, UV-VIS absorption and specific surface area. The characterization data were correlated to photocatalytic activities using turquoise blue dye (TBD) as model pollutant. With initial concentration of 30 ppm TBD, catalyst loading of 0.5 g/l, initial pH ~ 5.2, single doping (with Nb) and co-doping (Fe and Nb) catalyst have reached complete decolorization within 2.5 hours and 3 hours. And the kinetic reaction rate constant of apparent first-order model is 0.0258 min-1 and 0.0225 min-1, respectively.